International studies : interdisciplinary approaches - Aalto, Pami.; Harle, Vilho; Moisio, Sami. (Basingstoke : Palgrave Macmillan, 2011)
"Presenting International Studies as a wide, plural and inherently interdisciplinary field of research, this book shows its links with philosophy, peace research, history, geography, globalization studies, international political economy, political psychology, sociology and social theory, linguistics, strategic or war studies and anthropology"--
Machine generated contents note: -- PART I: GENERAL PERSPECTIVES -- Introduction / P. Aalto, V. Harle, D. Long & S. Moisio -- Interdisciplinarity and the Study of International Relations / D. Long -- Organizing Interdisciplinary International Studies: from Puzzlement to Research Programmes / P. Aalto -- Towards Interdisciplinary Research Programmes in International Studies: the Frankfurt School, the English School and Peace Research as Models / V. Harle -- PART II: LEVELS OF ANALYSIS -- Geographies of the International System: Globalization, Empire and the Anthropocene / S. Dalby -- Beyond the Domestic-International Divide: State Spatial Transformation as Neoliberal Geopolitics / S. Moisio -- The Human Subject in International Studies: an Outline for Interdisciplinary Research Programmes / P. Aalto -- PART III: CONCEPTS -- Power in International Relations: an Interdisciplinary Perspective / T. Forsberg -- War: from Disciplinarity to Multidisciplinarity and further to Transdisciplinarity / P. Drulak-- PART IV: END COMMENT -- End Comment: the Practices of Interdisciplinarity / I.B. Neumann..
Keywords: International relations. -- Research; International relations. -- Research. -- Methodology; kansainväliset suhteet; monitieteisyys; tutkimusohjelmat; tutkimusmenetelmät